Applications and Use of Diamond - Guodong, John (IntechOpen, 2023)
This book focuses on the latest developments and applications of diamond materials. It describes and discusses different types of diamond materials, including polycrystalline diamond, diamond thin films, graphite, graphene, and nanodiamond. The book also discusses diamond cutting and drilling tools, as well as presents breakthrough technologies for physicists, materials scientists, and engineers.